The Effect of Plantago major Rectal Suppository on Postpartum Hemorrhage Rate in Women at the Risk of Bleeding: A Single-blind Clinical Trial - Zahra Khojastehfard; Nahid Golmakani; Seyed Reza Mazloum; Shekveh Sadat Hamedi; Zohreh Feyzabadi; Masoumeh Mirteimouri (Mashhad University of Medical Sciences, 2019)
Introduction: Postpartum hemorrhage (PPH) is an obstetric emergency condition being known as one of the most common causes of maternal mortality throughout the world. Prevention from this problem can reduce mortality and side effects. One of the plants suggested as an antihemorrhagic agent in traditional medicine is Plantago. The aim of this study was to evaluate the effect of the rectal suppository of Plantago on postpartum hemorrhage rate in women at the risk of bleeding. Methods: This single-blind randomized clinical trial was performed on 70 pregnant women who were eligible for the study and referred to Umm al-Banin Hospital, Mashhad for vaginal delivery in 2018. In this study, the research population included high-risk women who, according to a prediction nomogram, had a chance of PPH with a score equal to or greater than 10. The participants were randomly divided into two groups of control and intervention with 35 subjects in each group. In both test and control groups, infusion of 30 units oxytocin in 1000 cc crystalloids was administered after delivery according to the hospital routine practice. In the intervention group, immediately after the expulsion of the placenta and fetal membranes and uterine massage, the first dose of rectal 120 mg suppositories of Plantago, followed by five doses with intervals of 30 min were given by the researchers. The amount of PPH was measured and recorded by weighing the blood bags and pads for 4 h after labor. All the data were analyzed using the SPSS software version 16. P-value < 0.05 was considered significant. Results: Our findings showed that the mean of bleeding 4 h after delivery in the control group was 306.2±11.21 cc and in the test group was 253.3±14.23 cc. This difference was found to be significant (P=0.001). Conclusion: According to the results of the present study, rectal Plantago suppository can be recommended as an effective medication for decreasing PPH in women at bleeding risk. In other words, it can be applied as an alternative for reducing bleeding in women at the risk of bleeding.